2020
DOI: 10.3389/fneur.2020.00102
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Activity Modulation During Post-operative Walking With Hybrid Assistive Limb (HAL) in a Patient With Thoracic Myelopathy Due to Ossification of Posterior Longitudinal Ligament: A Case Report

Abstract: Disorders of the central nervous system sometimes cause severe sensory motor paralysis accompanied by gait impairment. Recently, there are several reports on the effectiveness of robot-assisted gait training for patients experiencing these issues. The purpose of this case report was to assess the neuromechanical effect of a wearable robot suit HAL (Hybrid Assistive Limb) during post-operative gait training in a patient with gait impairment due to compressive myelopathy caused by ossification of the posterior l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Some previous studies have reported that HAL generates joint torques by amplifying the sensed muscle activity. 16 , 17 The patient’s ability to bear weight on his feet improved. We consider that HAL training with a sufficient amount of gait training might be used as a treatment for disuse syndrome in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have reported that HAL generates joint torques by amplifying the sensed muscle activity. 16 , 17 The patient’s ability to bear weight on his feet improved. We consider that HAL training with a sufficient amount of gait training might be used as a treatment for disuse syndrome in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…OPLL is not technically considered as causing lateral asymmetry, but patients usually develop asymmetrical gait since they tend to put more weight on a stronger leg and end up developing asymmetrical gait. In this sense, analysis of muscle synergy before and after HAL intervention may be a useful tool to evaluate muscle activity of OPLL patients (Kadone et al, 2020 ) after HAL intervention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the University of Houston used non-invasive brain-computer interface technology to control the Neuro Rex exoskeleton in real-time, explain the wearer's intention through EEG signals and finally achieve the goal of assisting paraplegic patients to complete walking independently [31]. The HAL exoskeleton developed by the University of Tsukuba in Japan can detect and obtain electrical signals generated by muscle movement on the skin surface, which was processed as input to the system control [32]. The third method comprehensively considers the advantages and disadvantages of the above two methods and establishes a man-machine sensor network to comprehensively utilize biological and motion signals.…”
Section: Motion Intention Perceptionmentioning
confidence: 99%